2021
DOI: 10.1371/journal.pone.0259333
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fast growing broiler chickens with a slower-growing breed type reared on Higher Welfare commercial farms

Abstract: Slowing the growth of modern broiler chickens can have a positive effect on a number of welfare outcomes. However, relatively few studies have compared fast and slower growing broiler chickens reared under the same commercial conditions. The main aim of this study was to evaluate a slower growing breed and standard fast growing broilers on commercial farms. Ross 308 broilers and slower growing Hubbard Redbro broilers were housed on six farms for 17 production cycles. Production data were available for all cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
60
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 34 publications
11
60
2
Order By: Relevance
“…However, Rayner et al (2020) observed less play in disturbed areas of the house in a fast-growing broiler strain than in 2 slower-growing strains, and this difference was accompanied by evidence of poorer health in the fast-growing flocks. Similar findings were reported by Baxter et al (2021) in a comparison of Hubbard Redbro vs. Ross 308 broilers.…”
Section: Playful Poultry: What Does It Take and What Does It Mean?supporting
confidence: 89%
See 1 more Smart Citation
“…However, Rayner et al (2020) observed less play in disturbed areas of the house in a fast-growing broiler strain than in 2 slower-growing strains, and this difference was accompanied by evidence of poorer health in the fast-growing flocks. Similar findings were reported by Baxter et al (2021) in a comparison of Hubbard Redbro vs. Ross 308 broilers.…”
Section: Playful Poultry: What Does It Take and What Does It Mean?supporting
confidence: 89%
“…The implication is that this type of play depends upon the availability of such items. Baxter et al (2021) found that striped red and white paper straw was effective in stimulating worm running during 1-min observations. Liu et al.…”
Section: Playful Poultry: What Does It Take and What Does It Mean?mentioning
confidence: 97%
“…Diet, together with genotype, age and sex of birds, and their management systems, is an important factor influencing animal growth and quality of production. Furthermore, focusing on well-being and housing conditions, chicken meat production is more oriented towards less intensive systems, for which medium- and slow-growing broiler strains have been recommended [ 7 ]. In fact, medium- and slow-growing chickens are more suitable for alternative production systems for their higher vitality, disease resistance, and adaptability to outdoor conditions than fast-growing chickens [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, throughout the world there is an increasing interest in alternative and less intensive poultry production systems that meet higher standards for animal welfare, for which medium- and slow-growing broiler strains have been recommended [ 17 ]. Indeed, several authors reported that medium- and slow-growing broiler strains perform better when referred to health issues than conventional strains [ 18 ], including more resilience to heat stress [ 19 ] and a meat more appropriate for a specialty or gourmet market [ 20 , 21 , 22 ]. The impact of the use of soybean meal and legume seeds in feed on the meat quality of fast-growing broiler chickens has been studied by other authors [ 8 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%